Performance of Modified Anaerobic Hybrid Baffled (MAHB) bioreactor treating recycled paper mill effluent: Effects of organic loading rates (Journal of Tropical Resources and Sustainable Science (JTRSS), 2018)
The performance of modified anaerobic hybrid baffled (MAHB) bioreactor treating recycled paper mill effluent (RPME) was investigated at various organic loading rates (OLR) of 1, 2, 3 and 4 g COD/ L.day. The bioreactor was operated continuously at constant hydraulic retention time (HRT) of a day without effluent recycled and chemicals adjustment/addition. Throughout 70 days of operation, a maximum removal efficiency up to 97% of chemical oxygen demand (COD) and 98% of volatile fatty acid, biogas production of 12.51 L/day equivalent to methane (CH4) yield of 0.108L CH4/ g COD and a stable pH system between 6.6 to 7.2 were achieved. Additionally, alkalinity of the bioreactor system shows a stable profile that indicates the whole system was well buffered with a quit high degradation of volatile solid (VS) up to 18%. These results indicated that MAHB bioreactor has been successfully treated RPME at various OLR.
Keywords: organic loading rate; anaerobic digestion; ecycled paper mill effluent; modified anaerobic hybrid baffled bioreactor